Abietane diterpenes from Abies spectabilis and their anti-pancreatic cancer activity against the MIA PaCa-2 cell line. (15th June 2022) - Phan, Nguyen Duy; Omar, Ashraf M.; Sun, Sijia; Maneenet, Juthamart; Dibwe, Dya Fita; Sato, Mao; Kalauni, Surya Kant; Toyooka, Naoki; Fujii, Tsutomu; Awale, Suresh
Graphical abstract: Abstract: An ethanolic extract of the stem of Abies spectabilis exhibited strong cytotoxicity against MIA PaCa-2 human pancreatic cancer cells preferentially under nutrient-deprived conditions. Therefore, phytochemical investigation of this bioactive extract was carried out, and that led the isolation of ten compounds (1 –10 ) including a new abietane-type diterpene (1 ). The structure of the new compound (1 ) was elucidated by combined spectroscopic techniques, including HRFABMS, NMR and quantum ECD calculation. All the isolated compounds were evaluated for their efficacy against MIA PaCa-2 human pancreatic cancer cell line by employing an anti-austerity strategy. Among the tested compounds, dehydroabietinol (5 ) displayed the most potent activity with a PC50 value of 6.6 μM. Dehydroabietinol (5 ) was also found to retard the MIA PaCa-2 cell migration under normal nutrient-rich conditions displaying its anti-metastatic potential. Investigation on the mechanism suggested that dehydroabietinol (5 ) is an inhibitor of the key cancer cell survival Akt/mTOR/autophagy signaling pathway.